2022
DOI: 10.1021/acs.chemmater.2c02266
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Phase Epitaxial Growth of Large-Area MAPbBr3–nCln/CsPbBr3 Perovskite Single-Crystal Heterojunction for Enhancing Sensitivity and Stability of X-ray Detector

Abstract: Metal halide perovskites have emerged as next-generation semiconductors for X-ray detection because of their excellent photoelectric properties. However, severe ion migration in three-dimensional (3D) halide perovskites usually causes dark current drift in radiation detectors, especially in high electric fields. Here, we report a liquid-phase epitaxial method based on inverse-temperature crystallization (ITC), with which a hybrid/all-inorganic 3D perovskite single-crystal heterojunction is constructed, using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…In the past decade, great progress has been made investigating halide perovskites as direct X-ray detectors and indirect X-ray detection scintillators. Currently, indirect-type X-ray detectors based on scintillators are mainstream products for X-ray detection and imaging equipment in the market due to their fast response time and easy integration with the well-known thin film transistor (TFT) and complementary metal oxide semiconductor (CMOS) photodetector arrays. Especially in portable X-ray detection equipment, indirect detectors have more advantages, particularly in cost, over direct X-ray detectors.…”
mentioning
confidence: 99%
“…In the past decade, great progress has been made investigating halide perovskites as direct X-ray detectors and indirect X-ray detection scintillators. Currently, indirect-type X-ray detectors based on scintillators are mainstream products for X-ray detection and imaging equipment in the market due to their fast response time and easy integration with the well-known thin film transistor (TFT) and complementary metal oxide semiconductor (CMOS) photodetector arrays. Especially in portable X-ray detection equipment, indirect detectors have more advantages, particularly in cost, over direct X-ray detectors.…”
mentioning
confidence: 99%
“…In addition to construct cascade structure, introducing wide gap layer at the interface between perovskite and electrode can generate higher potential barrier, prohibiting the injection of holes or electrons to suppress dark current. Zhou et al [38,39]also reported Cs 0.15 FA 0.85 Pb(I 0.15 Br 0.85 ) 3 /Cs 0.15 FA 0.85 PbI 3 heterojunction adopting dip coating process (Figure 3E). The device can inhibit dark current under X-ray illumination at reversed bias.…”
Section: Components Modificationmentioning
confidence: 97%
“…Additionally, except the research about heterojunction based on perovskite such as p-MAPbBr 3 /n-CsPbBr 3 [39], non-perovskite semiconductors can also provide abundant band structure candidates, including CuI [39], Te [40], etc. Although the above researches have been achieved, there still exist massive opportunities for future explore.…”
Section: Components Modificationmentioning
confidence: 99%
“…[ 6–8 ] 3D organometal perovskite single crystals (SCs) are the rising star due to the high absorption coefficient, [ 9 ] the long carrier diffusion length, [ 10,11 ] the low trap density, [ 12,13 ] and the ease of fabrication. [ 14,15 ] However, the ion migration in perovskite SCs, originating from the nature of ionic crystals and the high tolerance of the perovskite crystal structure, causes the current drift and deteriorate the device stability. [ 16–20 ] Suppressing the ion migration is critical and urgent for the future applications of perovskite single crystals.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] 3D organometal perovskite single crystals (SCs) are the rising star due to the high absorption coefficient, [9] the long carrier diffusion length, [10,11] the low trap density, [12,13] and the ease of fabrication. [14,15] However, the ion migration in perovskite SCs, originating from the nature of ionic crystals found that Br atoms in MAPbBr 3 migrate easier through vacancies than those in FAPbBr 3 because of the stronger H-bonding between FA ions with Br atoms. Bakr et al [11] observed a carrier diffusion length of 19.0 µm in FAPbBr 3 SCs, indicating the potential excellent capability of carrier collection.…”
Section: Introductionmentioning
confidence: 99%